New scanning technology reproduces rock art in 3D. (Research'eu results magazine)
To laypeople, prehistoric art is often pictured in the form of cave paintings. But rock art, another form of visual expression found in the open air, is more ubiquitous and often threatened by the whims of the weather. The 3D-PITOTI team has set out to ensure that this heritage continues to be passed on to future generations. Since 2013, it has been developing technologies able to scan, process, reconstruct and visualise rock in 3D.